2017
DOI: 10.1128/aac.01307-17
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HIV-1 Tat and Methamphetamine on Blood-Brain Barrier Integrity and FunctionIn Vitro

Abstract: Human immunodeficiency (HIV) infection results in neurocognitive deficits in about one half of infected individuals. Despite systemic effectiveness, restricted antiretroviral penetration across the blood-brain barrier (BBB) is a major limitation in fighting central nervous system (CNS)-localized infection. Drug abuse exacerbates HIV-induced cognitive and pathological CNS changes. This study's purpose was to investigate the effects of the HIV-1 protein Tat and methamphetamine on factors affecting drug penetrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 85 publications
(94 reference statements)
0
23
0
Order By: Relevance
“…29, 30 Apparent permeability ( P app ) was calculated using P app = (dX/dT • V r )/(A • C o ), where dX/dT is the mass of transported compound (X) over time (T), V r is the volume in the receiver compartment, A is the surface area of the membrane insert, and C o is the initial concentration in the donor compartment. 30 We first examined the potential cytotoxicity of 17 on hCMEC/D3 cells to rule out any potential interference with results interpretation, and the results demonstrated that 17 at 20 μM did not show significant toxic effects on these cells (Figure 7A). The apical-to-basolateral (A to B) and basolateral-to-apical (B to A) P app of 17 was 5.21 ± 0.56 × 10 −6 and 1.11 ± 0.12 × 10 −6 cm/sec, respectively (Figure 7B).…”
Section: Resultsmentioning
confidence: 99%
“…29, 30 Apparent permeability ( P app ) was calculated using P app = (dX/dT • V r )/(A • C o ), where dX/dT is the mass of transported compound (X) over time (T), V r is the volume in the receiver compartment, A is the surface area of the membrane insert, and C o is the initial concentration in the donor compartment. 30 We first examined the potential cytotoxicity of 17 on hCMEC/D3 cells to rule out any potential interference with results interpretation, and the results demonstrated that 17 at 20 μM did not show significant toxic effects on these cells (Figure 7A). The apical-to-basolateral (A to B) and basolateral-to-apical (B to A) P app of 17 was 5.21 ± 0.56 × 10 −6 and 1.11 ± 0.12 × 10 −6 cm/sec, respectively (Figure 7B).…”
Section: Resultsmentioning
confidence: 99%
“…However, following methamphetamine exposure, the pattern and distribution of staining was discontinuous, regardless of genotype. In a recent study by Patel et al , exposure to Tat and methamphetamine altered ZO-1 expression in an in vitro model of the blood-brain barrier; however, alterations in functional permeability were not obtained [ 49 ]. This suggests that alterations in the distribution and expression of multiple tight junction proteins may play a role in the functional permeability that was observed in the current in vivo study with non-Tg and Tg rats.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, limiting the bidirectional trafficking of HIV-infected macrophages into the CNS and restricting HIV replication within CNS compartments is of critical importance in reducing the production of viral proteins and limiting the CNS inflammation that drives HAND [ 64 ]. Of note, drug abuse exacerbates the pathological CNS changes found in patients with HAND [ 69 ]. For example, there is experimental and clinical evidence indicating that HIV neuropathogenesis and neurocognitive deficits are exacerbated with co-exposure to methamphetamine (meth) [ 63 ].…”
Section: The Influence Of Microglia In Disrupting and Compromising Thmentioning
confidence: 99%
“…Whereas monocyte-derived macrophages are most commonly used to model HIV-1 infection, HIV-1 replication has also been described in cultured primary microglia isolated from adult, infant, or foetal brains [ 125 ]. The presence of HIV-1 DNA has also been described in astrocytes and neurons isolated from HIV-1 encephalitis brain tissue by LCM [ 69 , 124 ]. However, it is not clear if this indicates a true latent infection or what role it might play in the pathogenesis of the infection.…”
Section: Role Of Inflammation In Hiv-associated Neurocognitive Disordmentioning
confidence: 99%